2021
DOI: 10.1155/2021/8834645
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Factors Mediating Neural Cell Plasticity Changes in Dementia Brain Diseases

Abstract: Neural plasticity—the ability to alter a neuronal response to environmental stimuli—is an important factor in learning and memory. Short-term synaptic plasticity and long-term synaptic plasticity, including long-term potentiation and long-term depression, are the most-characterized models of learning and memory at the molecular and cellular level. These processes are often disrupted by neurodegeneration-induced dementias. Alzheimer’s disease (AD) accounts for 50% of cases of dementia. Vascular dementia (VaD), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 169 publications
0
6
0
Order By: Relevance
“… 61 Molecular modifications in the hippocampus, such as microglial activation, decreased neurogenesis and apoptosis, are directly related to the onset of dementia. 61 , 62 Moreover, studies using diet-induced obesity models demonstrated that neuroinflammation is an important feature of obesity, including in the hippocampus, 63 that is associated with decreased neurogenesis, 15 , 64 cognitive impairment 56 , 65 and activation of apoptosis. 66 In obesity, adipocytes produce pro-inflammatory cytokines that can cross the blood–brain barrier (BBB) and induce microglial activation and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“… 61 Molecular modifications in the hippocampus, such as microglial activation, decreased neurogenesis and apoptosis, are directly related to the onset of dementia. 61 , 62 Moreover, studies using diet-induced obesity models demonstrated that neuroinflammation is an important feature of obesity, including in the hippocampus, 63 that is associated with decreased neurogenesis, 15 , 64 cognitive impairment 56 , 65 and activation of apoptosis. 66 In obesity, adipocytes produce pro-inflammatory cytokines that can cross the blood–brain barrier (BBB) and induce microglial activation and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is the most sensitive region of the brain and most susceptible to ischemia and hypoxia, particularly the CA1 region [45]. Various brain areas work in coordination for different types of cognitive functions [46]. Other than the hippocampal area, the entorhinal cortex, prefrontal cortex, cerebellum, septum, amygdala, and pons play a crucial role in memory function.…”
Section: Discussionmentioning
confidence: 99%
“…These organelles convert energy to adenosine triphosphate (ATP), which neurons need to regulate, among other neurotransmissions [ 1 ]. Moreover, ATP plays a crucial role in processes related to maintaining neuronal plasticity [ 7 , 8 ]. Mitochondria are not only the main energy producers in cells but also the main source of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%